An innovation capacity analysis to identify strategies for improving plantain and banana (Musa spp.) productivity and value addition in the Democratic Republic of Congo - Hauser, S.; Dheda, B.; Vangu, G.; Mobambo, P.; Staver, Charles (2010)
The agricultural sector of the Democratic Republic of Congo continues tosuffer from declining productivity after a decade of civil unrest andunderinvestment. Plantain and banana (Musa spp.) are considered the second mostimportant staple crop after cassava (Manihot esculenta). The Congo basin is asecondary centre of plantain diversity in the world. The area planted withplantain/banana declined from over 400,000 ha in the early 90s to less than 150,000ha presently. Yields are low and declining and plantain become too expensive forpoor urban households. There are numerous political, economic, social andtechnological constraints to increase the contribution of banana and plantain tohousehold, community and the national economy. A number of priorities for actionwere identified: (a) simple and low cost strategies to estimate production andplanted areas and the extent of serious pest and disease threats to guide investmentin areas with the greatest impact; (b) mapping of production potential based onsoils, climate and water sources and ease of market access to prioritize investment inintensification; (c) piloting of clean seed systems to contain the spread and impact ofBanana bunchy top virus, and Xanthomonas wilt, to multiply highly productiveclones of preferred cultivars and to conserve plantain diversity; (d) technology forland productivity stabilization and improvement, depending on access toinfrastructure and natural resource quality; (e) improving field access toinformation on new technologies to farmers and their associations, public extensionand non-governmental organizations and rural school teachers; and (f) farmer andvillage marketing organizations to capture greater value from plantain and bananamarkets where clean seed and improved land productivity are piloted.